2016
DOI: 10.1016/j.neucom.2015.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Applying subclustering and Lp distance in Weighted K-Means with distributed centroids

Abstract: We consider the weighted K-Means algorithm with distributed centroids aimed at clustering data sets with numerical, categorical and mixed types of data. Our approach allows given features (i.e., variables) to have different weights at different clusters. Thus, it supports the intuitive idea that features may have different degrees of relevance at different clusters. We use the Minkowski metric in a way that feature weights become feature re-scaling factors for any considered exponent. Moreover, the traditional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 21 publications
0
15
0
1
Order By: Relevance
“…The noise model 1 addresses the issue of generic clustering methods based on the least-squares criterion (2): they cannot distinguish between useful and inadequate features. It has been used in [11,8,9,10] to test the weighted feature versions of k-means and Ward algorithms; those showed good cluster recovery properties against such noise features. The noise model 2 is novel.…”
Section: Comparing Ward and A-wardmentioning
confidence: 99%
See 2 more Smart Citations
“…The noise model 1 addresses the issue of generic clustering methods based on the least-squares criterion (2): they cannot distinguish between useful and inadequate features. It has been used in [11,8,9,10] to test the weighted feature versions of k-means and Ward algorithms; those showed good cluster recovery properties against such noise features. The noise model 2 is novel.…”
Section: Comparing Ward and A-wardmentioning
confidence: 99%
“…Analogously to our previous simulation studies [10,8], we first found a set of partitions, each corresponding to a different combination of values of p and β. The set of all possible values of p and β was modelled using a grid of p and β values varying from 1.1 to 5.0 with the step of 0.1, as in [11].…”
Section: Validation Of the A-ward Pβ Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…The k-means algorithm runs inconvenient time if it is based on the histogram-based approaches [2,3]. A histogram shows the number of elements such that each has the same attributes.…”
Section: Introductionmentioning
confidence: 99%
“…The main goal of the clustering methods is to group the given data according to their similarities so that the elements of any group will be similar entities (de Amorim and Makarenkov, 2016). To solve many practical problems, such as image segmentation, the clustering methods are commonly used in image processing applications.…”
Section: Introductionmentioning
confidence: 99%